Mr. Putter & Tabby : Feed the fish - Rylant, Cynthia; Howard, Arthur (San Diego : Harcourt, 2001)
After Mr. Putter buys three goldfish and takes them home, he discovers that his cat Tabby has a serious problem with them.
Booklist
Kirkus Starred
School Library Journal starred
Booklist, May 2001
Kirkus Starred, January 2001
School Library Journal starred, May 2001
Keywords: Cats -- Fiction; Goldfish -- Fiction; Putter, Mr. (Fictitious character) -- Fiction; Tabby (Fictitious character : Rylant) -- Fiction; Cats -- Fiction; Goldfish -- Fiction; Putter, Mr. (Fictional character) -- Fiction; Tabby (Fictitious character : Rylant) -- Fiction